Modelling the piezo-protection effect exerted by lactate on the high pressure resistance of Listeria monocytogenes in cooked ham. (February 2021) - Serra-Castelló, Cristina; Jofré, Anna; Belletti, Nicoletta; Garriga, Margarita; Bover-Cid, Sara
Graphical abstract: Highlights: HPP lethality as a function of duration, product formulation and strain was modelled. Different L. monocytogenes strains showed convex, linear and concave inactivation shapes. Potassium lactate protected L. monocytogenes from HPP inactivation. The piezo-protection of lactate showed a quadratic dose-dependent effect on δ. Abstract: Food safety is often based on the application of several preservative (hurdle) factors whose combination must be smartly selected. The aim of the present study was to evaluate the effect of lactate and diacetate on the high pressure processing (HPP) inactivation of three L. monocytogenes strains (CTC1011, CTC1034 and Scott A) in sliced cooked ham. Inoculated vacuum-packed slices of cooked ham formulated without organic acids and with lactate, diacetate or the combination of both were pressurized at 400 MPa for different holding times and the inactivation kinetics were characterised by fitting primary and secondary models. The shape of the inactivation curves for L. monocytogenes depended on both product formulation and strain. Interestingly, lactate caused a dose-dependent piezo-protection in all three strains, as the HPP inactivation rate decreased in cooked ham formulated with increasing amounts of lactate and in comparison with the control product. The design, validation and implementation of HPP requires a tailor-made approach, considering product formulation and selection of strain/s.